Mental health service use and its associated factors among nurses in China: a cross-sectional survey - Tian, Yusheng; Yue, Yuchen; Liao, Xiaoli; Wang, Jianjian; Ye, Man; Liu, Yiting; Li, Yamin; Zhou, Jiansong (PeerJ, 2021)
Background To facilitate mental health service planning for nurses, data on the patterns of mental health service use (MHSU) among nurses are needed. However, MHSU among Chinese nurses has seldom been studied. Our study aimed to explore the rate of MHSU among Chinese nurses and to identify the factors associated with MHSU. Methods A self-designed anonymous questionnaire was used in this study. MHSU was assessed by the question, “Have you ever used any kind of mental health services, such as mental health outpatient services or psychotherapies, when you felt that your health was suffering due to stress, insomnia, or other reasons?” The answer to the question was binary (yes or no). Sleep quality, burnout, and depressive symptoms were assessed using the Chinese version of the Pittsburgh Sleep Quality Index , the Chinese version of the Maslach Burnout Inventory-General Survey and the two-item Patient Health Questionnaire, respectively. Chi-square tests and binary logistic regression were used for univariate and multivariate analyses. Results A total of 10.94% (301/2750) of the nurses reported MHSU. 10.25% (282/2750) of the nurses had poor sleep quality, burnout and depressive symptoms, and only 26.95% of these nurses reported MHSU. Very poor sleep quality (OR 9.36, 95% CI [5.38-16.29]), mid-level professional title (OR 1.48, 95% CI [1.13-1.93]) and depressive symptoms (OR 1.66, 95% CI [1.28-2.13]) were independent factors associated with MHSU. Conclusions Most of the nurses have experienced burnout, poor sleep quality or depressive symptoms and the MHSU rate among them was low. Interventions to improve the mental health of nurses and to promote the use of mental health services are needed.
Keywords: Nurse; Sleep quality; Burnout; Depression; Mental health service use